On various ways of measuring unemployment, with applications to Switzerland - Joseph Deutsch; Yves Flückiger; Jacques Silber (Levy Economics Institute of Bard College, 2007)
This paper begins with an examination of various ways of measuring unemployment and, borrowing ideas from the poverty measurement literature, proposes four new general unemployment indices. The first of these is parallel to the Sen poverty index; the second, to the Sen index's generalization by Shorrocks; the third, to the FGT poverty index; and the fourth, to the Watts poverty index. The authors then present an empirical illustration based on Swiss data compiled at the state, or canton, level, using the so-called Shapley decomposition to determine the contribution of three componentsthe traditional unemployment rate, the average unemployment duration, and the inequality in the unemployment durationsto the differences between the values of the four proposed indices, both within a given canton and within Switzerland as a whole. The paper concludes with a discussion of the assumptions made about the maximum unemployment duration for the purposes of the study, and their impact on the results obtained.
Keywords: I32; J64; 330; FGT Poverty Index; Inequality; Sen Pverty Index; Shapley Decomposition; Switzerland; Unemployment Duration; Watts Poverty Index; Arbeitslosigkeit; Messung; Teilstaat; Schweiz